Pengembangan Sistem Monitoring Transaksi Sewa dan Pemeliharaan Mobil berbasis Android (Studi Kasus: PT. Belfano Nahla Utama) - Bella Rhobiatul Adhawiyah; Agi Putra Kharisma; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Car rental is a temporary agreement with payment to use someone else's car. People choose rentals because they cannot buy their own or require several cars at once. If there are more requests for rentals, it's harder to remember which car rentals will end. PT Belfano Nahla Utama is a car rental company with hundreds of cars but still doesn't have an automation system. So they can have difficulty for monitoring and reminding the validity period of contracts, bills, vehicle registration, vehicle inspection, and car service. They can suffer losses because they forget to ask for payment or return the car. They also can get fines for being late in extending car maintenance documents. The author develops an Android application with Push Notifications and a Prototype approach to solving the problem with a better understanding of the system. There are 21 functional and 2 non-functional requirements obtained. Usability testing using System Usability Scale (SUS) questionnaire produces an average score of 83 by 5 employees means Good or B rank and an average score of 91.25 by 2 owners means Excellent or A rank. Black Box testing with 34 test cases producing 91.2% valid. Compatibility testing has 100% valid results.